Penguatan Kapasitas Konselor Sebaya, Edukasi, dan Dukungan Psikososial Berbasis Komunitas HIV Melalui Platform VIDA Digital - Mamat Abas; Sitty Khairun Nisa Tahir Rauf; Ukhti Nurfajriah Sasmita Ijonu; Iken Meyti Katili (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aimed to strengthen the capacity of peer counselors in providing education and psychosocial support for people living with HIV/AIDS (PLWHA) through the utilization of the VIDA Digital Platform. The method used was a participatory approach with a pre-experimental design (one group pretest–posttest). The activity was carried out through several stages, including participant recruitment, pre-test, training and education, role-playing sessions, and post-test evaluation. A total of 56 students from Universitas Negeri Gorontalo participated as peer counselor candidates. The results showed a significant improvement in participants’ knowledge and understanding, indicated by an increase in average scores from moderate in the pre-test to good and very good categories in the post-test. In addition, participants demonstrated improved empathetic communication skills and readiness to provide psychosocial support. The introduction of the VIDA Digital Platform further enhanced participants’ ability to deliver technology-based services